The impact of modern trends in education on the use of learning strategies for people with mental disabilities for the secondary stage from the point of view of teachers in the city of Makkah - Al-Sowat, Hanaa Fahad (Journal of Educational and Psychological Sciences, 2024)
The research aims to clarify the impact of modern educational trends in the use of learning strategies for people with mild mental disabilities for the secondary stage. It also helps educational decision makers prepare special programs for teaching people with mental disabilities from the point of view of teachers. The descriptive approach was used to achieve the research objectives, and a questionnaire consisting of (10) phrases and distributed them to (15) teachers. One of the most important findings that the Researcher reached was the importance of modern learning strategies, as they contribute to supporting the teacher while explaining to people with mental disabilities. They also help students acquire new skills and knowledge better than traditional education and give the student self-confidence. It increases the interaction of people with mental disabilities within the classroom. The Researcher recommends increasing teachers’ awareness of modern learning strategies and how to apply and activate them for students with mental disabilities, such as grading from simple to complex, dividing materials into parts, and providing continuous feedback and reinforcement.